Pyroptosis and inflammasomes in diabetic wound healing - Mu, Xingrui; Wu, Xingqian; He, Wenjie; Liu, Ye; Wu, Faming; Nie, Xuqiang (Frontiers in Endocrinology, 2022)
Diabetic wound is one of the complications of diabetes and is not easy to heal. It often evolves into chronic ulcers, and severe patients will face amputation. Compared with normal wounds, diabetic wounds have an increased proportion of pro-inflammatory cytokines that are detrimental to the normal healing response. The burden of this disease on patients and healthcare providers is overwhelming, and practical solutions for managing and treating diabetic wounds are urgently needed. Pyroptosis, an inflammatory type of programmed cell death, is usually triggered by the inflammasome. The pyroptosis-driven cell death process is primarily mediated by the traditional signaling pathway caused by caspase -1 and the non-classical signaling pathways induced by caspase -4/5/11. Growing evidence that pyroptosis-induced cell death promotes diabetic complications, including diabetic wounds. In addition, inflammation is thought to be detrimental to wound healing. It is worth noting that the activation of the NLRP3 inflammasome plays a crucial role in the recovery of diabetic wounds. This review describes the mechanisms of pyroptosis-related signaling pathways and their impact on diabetic wounds. It discusses new theories and approaches to promote diabetic wound healing, as well as some potential compounds targeting pyroptosis and inflammasome signaling pathways that could be new approaches to treating diabetic wounds.